A multi-analytical approach to the examination of nineteenth-century European wallpapers in Vasiq-Ansari House in Isfahan, Iran. (May 2014) - Holakooei, Parviz; Karimy, Amir-Hossein; Vaccaro, Carmela
<x content-type="archive" xml:space="preserve">Abstract</x> In the nineteenth century, imported wallpapers covered interior walls of Persian palaces and mansions, of which Vasiq-Ansari House in Isfahan, Iran, exhibits very highly elaborated examples. In this study, micro-Raman spectroscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy, ultraviolet–visible spectroscopy, and light microscopy were used to identify pigments and other materials used in the wallpapers of Vasiq-Ansari House. Results indicated that chrome yellow, artificial ultramarine blue, brass metallic leaf, an organic red dyestuff (probably cochineal), and a copper-based green were used as colourants in the wallpapers. Different shades of brown were achieved by mixing various combinations of red lead, carbon black, and calcium carbonate. The white calcium carbonate was also used as a ground layer, applied to a paper support composed of bast and softwood fibres. Based on knowledge of the materials used, these wallpapers are most probably manufactured from the mid- to late-nineteenth century.